2015
DOI: 10.1590/1678-775720140074
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Class III malocclusion treated with maxillary expansion, facemask therapy and corrective orthodontic. A 15-year follow-up

Abstract: The facial growth of Class III malocclusion worsens with age, in this case, the early orthopedic treatment, providing facial balance, modifying the maxillofacial growth and development. A 7.6-year old boy presented with Class III malocclusion associated with anterior crossbite; the mandible was shifted to the right and the maxilla had a transversal deficiency. Rapid maxillary expansion followed by facemask therapy was performed, to correct the anteroposterior relationship and improve the facial profile. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…In addition, it is described in the literature that Class III discrepancy worsens with age, with growth of the maxilla ending earlier than that of the mandible. After the rapid palatal expansion phase, Class III correction protocols involve the application of the facial mask to initiate maxillary advancement using 5/16-inch elastics with an applied force of 200 g for the first week and then 500 g for 20 h per day for 6 months [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is described in the literature that Class III discrepancy worsens with age, with growth of the maxilla ending earlier than that of the mandible. After the rapid palatal expansion phase, Class III correction protocols involve the application of the facial mask to initiate maxillary advancement using 5/16-inch elastics with an applied force of 200 g for the first week and then 500 g for 20 h per day for 6 months [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…16,20,21 Bu görüşün aksine Sınıf 3 maloklüzyonun düzeltilmesinden sonra uygun oklüzal ilişkiler sağlandığında üst çenenin alt çenedeki büyümeye ayak uydurduğunu ve bu uyumun büyüme döneminin sonuna kadar devam ederek Sınıf 1 ilişkiyi koruduğu da bildirilmektedir. 22,23 Bu nedenle bu çalışmada Sınıf 3 maloklüzyonların büyüme ve gelişim döneminde hızlı üst çene genişletmesi ve ortopedik yüz maskesi yöntemi ile düzeltilmesinin ve sonrasında uygulanan sabit ortodontik tedavinin etkile-rinin ve kalıcılığının değerlendirilmesi amaçlanmıştır.…”
Section: Discussionunclassified
“…Class III malocclusion in mixed dentition is one of the most challenging situations for orthodontists, mainly for the uncertainly of stable long-term results owing to the interaction of both genetic inheritance and environmental factors (D'Apuzzo et al, 2019). Due to the increasing trend of growth and development, it has been widely reported that active intervene of Class III malocclusion in the early stage can improve the appearance of the patients, reduce the degree of deformity and promote the coordinated development of soft and hard tissues (Almeida et al, 2015;Tseng et al, 2016). Although there are some defects in FR-3 appliance, such as discomfort in large size, it is still an important means in the orthodontic treatment of Class III malocclusion, especially in mixed dentition, because the mechanism of FR-3 appliance is that the lip pads and buccal shields can relieve the development of the upper arch of the periorbital muscle, and to stretch the periosteum of the vestibular mucosa to stimulate bone hyperplasia and stimulate the growth of alveolar and basal bone (Ngan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%